Adipose Tissue Myeloid-Lineage Neuroimmune Cells Express Genes Important for Neural Plasticity and Regulate Adipose Innervation - Blaszkiewicz, Magdalena; Gunsch, Gilian; Willows, Jake W.; Gardner, Miranda L.; Sepeda, Jesse A.; Sas, Andrew R.; Townsend, Kristy L. (Frontiers in Endocrinology, 2022)
Peripheral nerves allow bidirectional communication between brain and adipose tissues, and many studies have clearly demonstrated that loss of the adipose nerve supply results in tissue dysfunction and metabolic dysregulation. Neuroimmune cells closely associate with nerves in many tissues, including subcutaneous white adipose tissue (scWAT), however, in scWAT their functions remain largely unexplored beyond degrading norepinephrine in an obese state. We previously reported that a myeloid-lineage knockout (KO) of brain derived neurotrophic factor (BDNF) resulted in decreased innervation of scWAT, accompanied by an inability to brown scWAT after cold stimulation and increased adiposity after a high fat diet. These data underscored that adipose tissue neuroimmune cells support the peripheral nerve supply to adipose and impact the tissue’s metabolic functions. We also reported that a subset of myeloid lineage monocyte/macrophages (Ly6c+CCR2+Cx3cr1+) are recruited to scWAT in response to cold, a process known to increase neurite density in adipose and promote metabolically healthy processes. These cold induced neuroimmune cells (CINCs) also expressed BDNF. Here, we performed RNAseq on CINCs from cold exposed and room temperature housed mice, which revealed a striking and coordinated differential expression of numerous genes involved in neuronal function, including neurotrophin signaling and axonal guidance, further supporting that CINCs fulfill a nerve supporting role in adipose. Increased expression of leukocyte transendothelial migration genes in cold stimulated CINCs also confirm prior evidence that they are recruited to scWAT and are not tissue-resident. We now provide whole depot imaging of scWAT from LysM-BDNF KO mice, revealing a striking reduction of innervation across the depot fitting with their reduced energy expenditure phenotype. By contrast, Cx3cr1-BDNF KO mice (a macrophage subset of LysM+ cells) exhibited increased thermogenesis and energy expenditure, with compensatory increased food intake and no change in adiposity or body weight. While these KO mice also exhibit significantly reduced innervation of scWAT, especially around the subiliac lymph node (SiLN), they displayed an increase in small fiber sympathetic neurite branching, which may underlie their increased thermogenesis. Together, we propose a homeostatic role of scWAT myeloid-lineage neuroimmune cells in nerve maintenance and neuro-adipose regulation of energy expenditure.